VIDEO SURVEILLANCE AND ARTIFICIAL INTELLIGENCE: HOW DOES IT AFFECT PRIVACY AND INTELLECTUAL PROPERTY RIGHTS? - Mihăilă, Carmen Oana; Mihăilă, Mircea (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The protection of individual privacy is increasingly questioned in the context of today’s high-tech video surveillance by using superior technologies, such as Artificial Intelligence (smart cameras and video surveillance systems, biometrics and facial recognition) which is capable of analyzing a huge amount of data, identifying links between these data and de-anonymizing them. Technology is synonymous with evolution. Yet, the advantages of using new technology are combined with great risks. The use of video cameras for surveillance raises important privacy issues. Biometric remote identification can only be performed under certain safeguards, in the context of a justified interest and with respect for the principle of proportionality. In recent years, facial recognition technology has become increasingly widespread, and highly controversial, as it is omnipresent (at airport check-in lines, police departments, pharmacies, etc.). While it may add a sense of security and comfort for businesses implementing it, such technology has been widely criticized by privacy advocates, especially for its built-in racial bias and potential for abusive use. "Real-time" biometric identification of individuals in public-accessible spaces for law enforcement purposes is seen as highly intrusive on the rights and freedoms of the individuals concerned, but it also evokes a sense of constant surveillance and indirectly discourages the exercise of freedom of assembly and other fundamental rights. Another important issue is the use of video surveillance in a context where it can cause problems in terms of intellectual property. The unauthorized use of recordings may affect confidential business operations. Trade secrets and confidential information are often an essential part of a company’s intellectual property portfolio. Thus, companies have to take extra steps to ensure that images captured by cameras are stored securely and accessible only to authorized personnel. Cameras can capture images of artistic works, performances, exhibitions, and uncontrolled access can lead to infringement of copyright and related rights. As captured videos can be uploaded to platforms, such use of intellectual property can lead to copyright infringement, especially when the video entails the use of copyrighted material without the owner’s permission, which constitutes an infringement of intellectual property rights.